Capacitação de pais e professores para ações integradas de ensino de leitura e escrita para aprendizes com autismo e deficiência intelectual - Benitez-Afonso, Priscila (2015)
This dissertation was written in the compendium of scientific texts and introduces three studies that support the planning, implementation and evaluation of interventions to ensure academic learning of reading and writing basic skills for learners with intellectual disabilities (ID) and autistic spectrum disorder (ASD), from the involvement of three different educational agents (regular classroom teachers, special education teachers and parents). First, we proposed a systematic review of national literature about the role of educational agents (Study 1). From the lack of studies that aimed teaching reading and writing basic skills by educational agents, we were proposed a discussion on the role of formal and informal agents, in order to identify the behavior of the agents as applicators reading and writing tasks to students with ID and ASD. Following were scheduled four interventions applied by each of the educational agents with each student (Study 2) then proposed a joint training with all agents and evaluated the reading performances and writing of students when exposed the interventions implemented by them together (Study 3). The suggestions are proposed for conducting future studies and it is expected that the results may assist in the elaboration of teaching reading and writing interventions for learners with ID and ASD from the joint participation of the three educational agents: regular classroom teachers, special education teachers and parents.